2022
DOI: 10.1128/aem.00044-22
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Klebsiella variicola Isolated in the Urine of Healthy Bovine Heifers, a Potential Risk as an Emerging Human Pathogen

Abstract: Klebsiella variicola is an opportunistic pathogen in humans. It also has been associated with bovine mastitis, which can have significant economic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…25 As well, the circulation of multidrug-resistant K. variicola in healthy livestock animals has also been reported. 26 Contrary to the existing studies that investigate the role of K. variicola in environmental resistance and animal disease, there is growing evidence of its clinical impact. Previous research has demonstrated that K. variicola is associated with a range of infections, including bloodstream infections, urinary infections, and respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…25 As well, the circulation of multidrug-resistant K. variicola in healthy livestock animals has also been reported. 26 Contrary to the existing studies that investigate the role of K. variicola in environmental resistance and animal disease, there is growing evidence of its clinical impact. Previous research has demonstrated that K. variicola is associated with a range of infections, including bloodstream infections, urinary infections, and respiratory tract infections.…”
Section: Discussionmentioning
confidence: 99%
“…While Klebsiella pneumoniae species complex (KpSC) members are clinically relevant as opportunistic human pathogens ( 1 ) with intrinsic resistance to penicillins ( 2 , 3 ) often extending to cephalosporins ( 4 , 5 ) and carbapenems ( 6 , 7 ), they are also found as endophytes ( 8 ). Kingdom-crossing is especially pronounced in strains of K. variicola ( 9 ), which are not only nitrogen fixers and plant colonizers, isolated from sources such as sugarcane ( 10 ), rice and bananas ( 11 ), but also found in bloodstream infections ( 12 ), cattle urine ( 13 ) and termite gut microbiota ( 14 ).…”
Section: Announcementmentioning
confidence: 99%
“…The latter is commonly isolated as part of plant microbiomes as it can promote plant growth by nitrogen fixation (Pinto-Tomás et al 2009 ). It is also an emerging human pathogen (Rodríguez-Medina et al 2019 ) causing urinary tract infections (Potter et al 2018 ), as well as in other diseases in wild and farm animals (Giannattasio-Ferraz et al 2022 ). However, K. variicola has been largely neglected due to a historic taxonomic misclassification (Martínez-Romero et al 2018 , Rodrigues et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%